Diagnóstico de las unidades de producción de camarón en tierras adentro en la provincia de El Oro - Figueroa MAldonado, Rommel P. (2005)
The present work was carried out in the south part of the Ecuador, County of El Oro, specifically in the cantons (Arenillas , Sta. Rosa, The Guabo and Machala), thinking about the following objectives: 1. To quantify the number and extension of the camaroneras existent lands inside; 2. To determine the main conditions under those which they are exploited in the County of El Oro; 3. To determine the production of the camaroneras lands inside in the County of El Oro. The study universe was the total of those producing of shrimp lands inside and members associated to the Camera of Producing of Shrimp, for him which he/she took the listing of associated of both institutions to this institution. For their development it was elaborated surveys directed inside at 16 producing of shrimp lands whose farms are located in the cantons (Arenillas Sta. Rosa, The Guabo, Machala) of the county of El Oro, and in turn; to the institutions that somehow are inside related with the activity acuícola lands. For the process of the surveys he/she was carried out the analysis of the variables by means of descriptive squares, summaries of an or more variable in study, in those that are detailed, averages, percentages, bars, pastries and histograms of frequency; this way, it was allowed to know the real situation of those producing of shrimp lands inside the County of El Oro. It was determined that the main obstacle of the sector was the price of the existent shrimp, then the presence of the virus of the white stain and the lack of the government's support; besides the investigation lack on the part of its technicians for that it will be this way difficult to maintain to the industry acuícola floats.